2004
DOI: 10.1051/agro:2004041
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impacts of extensification of grassland management on biodiversity and productivity in upland areas. A review

Abstract: Modern rural policies that incorporate agricultural and environmental aims within the broader framework of sustainable rural development are being formulated to address the problem of declines in grassland biodiversity and the destruction of sensitive landscapes and habitats in Europe. Extensification is the process of reducing fertiliser inputs, management intensity and stocking rates, and is central to these sustainable rural policies. However, research in the Less Favoured Areas of Europe has been fragmente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 52 publications
2
65
0
2
Order By: Relevance
“…This contrasts with the conclusions from surveys analyzing the effect of fertilizer cessation as an opportunity for restoring plant community diversity in fertile grasslands. Marriott et al (2004) and Tallowin et al (2005) found no great difference in the structure and composition between intensive grasslands and extensive grasslands that had been managed intensively in the past. High nutrient availability is indeed a major factor limiting the restoral of greater plant diversity in temperate grasslands (Janssens et al, 1998;Bakker and Berendse, 1999;Suding et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This contrasts with the conclusions from surveys analyzing the effect of fertilizer cessation as an opportunity for restoring plant community diversity in fertile grasslands. Marriott et al (2004) and Tallowin et al (2005) found no great difference in the structure and composition between intensive grasslands and extensive grasslands that had been managed intensively in the past. High nutrient availability is indeed a major factor limiting the restoral of greater plant diversity in temperate grasslands (Janssens et al, 1998;Bakker and Berendse, 1999;Suding et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
“…In upper alpine grasslands, stress-tolerant species, plants with low nutritive value and mosses declined after sheep exclusion (Mayer et al, 2009). In contrast to abandonment, reported changes in species composition were much slower when stocking rate was manipulated (Hulme et al, 1999;Marriott et al, 2004;Scimone et al, 2007). This was, for example, the case over the first 5 years of measurements in extensively used ryegrass/white clover sown swards (Marriott et al, 2002), although this last survey did find long-term patterns with A. capillaris, Poa trivialis, Festuca rubra and Holcus lanatus being favored by a reduction in stocking rate, whereas more competitive or ruderal species such as T. repens and Poa annua increased with increasing stocking rate (Marriott et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Sward heterogeneity was systematically higher than that in plots grazed at a low stocking rate, with more than 15% of plot area kept at a reproductive stage at the end of the grazing season. This patch mosaic is expected to favour vegetation and insect diversity by providing resources for species characteristic of short as well as tall vegetation, with reduced disturbance for plant species that are less tolerant to grazing (Grime, 1979;Marriott et al, 2004), and increased habitat quality for insects requiring buffered microclimates (Wallis De Vries et al, 2007). Hence, it could represent the optimal balance to satisfy both livestock production and conservation management objectives.…”
Section: Discussionmentioning
confidence: 99%
“…This has been confirmed by surveys of changes in the botanical composition of pastures following a reduction of management intensity or stocking rates (e.g. Kiehl et al, 1996;Hart and Ashby, 1998;Marriott et al, 2004). However, a very low stocking rate is also assumed to reduce plant diversity as a result of competitive exclusion, where the high productivity of some species dominates plant species that cannot compete for light (Grime, 1979).…”
Section: Introductionmentioning
confidence: 89%
“…Additional nutrients are also applied to improved grassland in upland systems and, given the harsher growing conditions and shorter growing season in such areas, these applications are often crucial for maintaining overall system productivity. In line with this view, Fothergill et al (2001) and Marriott et al (2004) demonstrated substantial negative effects on sward carrying capacity and animal performance when such additional nutrients are withdrawn. The inputs of resources, and of N-fertilisers in particular, can be substantial and can result in a large N surplus, which is lost through leaching as nitrate or as gaseous N emissions.…”
Section: Impact Of Grazing On Biodiversity and Environmental Charactementioning
confidence: 59%